Management of Perioperative Anticoagulation in Patients with Hip Fracture and Atrial Fibrillation (Revista de Medicina Clinica, 2019)
Aim: To investigate the incidence of hemorrhagic and cardiovascular complications in hospitalized patients with hip fracture (HF) anticoagulated with atrial fibrillation (AF). To evaluate the transfusion, anticoagulation pre-surgery management and its relationship with the complications.Methods: 18-month observational and retrospective study of hospitalized patients over 70 with HF and AF who have received an anticoagulant treatment and did not suffer from anemia in the previous 6 months. Severe anemia was considered Hb